Exploration of Graphene in the Medical Field: Research Progress and Future Prospects of Disease Diagnosis and Treatment and Medical Devices - Jiao Yuxuan; Kong Xiangjun; Tan Chen; Wang Xianghui (MATEC Web of Conferences)
As the medical demand continues to rise, the limitations of traditional medical materials in terms of accuracy, sensitivity, and durability have become increasingly prominent, making it difficult to meet the development needs of precision medicine. This paper comprehensively reviews the progress of graphene research in the medical field. This study explores its applications in disease diagnosis and treatment, such as biological detection, construction of drug and gene carriers, phototherapy, and biological imaging, as well as in medical devices, including tissue engineering, biosensors, and wearable devices. With its excellent thermal conductivity, electrical conductivity, and remarkable mechanical strength, graphene has effectively promoted innovation in medical diagnosis and treatment. However, there are still many limitations. It has poor immunebiocompatibility, and it is difficult to precisely regulate the immune response; its degradation is slow and difficult to control, and it is prone to accumulate and affect organs; the internal environment restricts targeted delivery, and the technology is not yet mature; the signal is unstable when used in biosensors; and it fails to meet the clinical requirements in the field of nerve repair. It is hoped that this paper can provide ideas for subsequent research and promote the further utilization of graphene in the medical field.